(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Samples of pristine poly vinyl chloride (PVC) and other samples of the same matrix containing a variable amount of inorganic sodium salt (sodium chloride NaCl) were prepared via simple casting route in a dimethyl sulfoxide (DMSO) solvent were prepared. Prepared samples were characterized via x-ray diffraction (XRD) measurements and Fourier transform infrared spectrophotometric measurements (FTIR) in combination with computational density functional theory approaches (DFT) into account for a detailed picture of the possible reaction mechanisms within the polymeric matrices. All measurements were performed on the possible basis set. Local density approximate (LDA) and generalized Goertzel algorithm (GGA) was also tested. A compatibility between computed and experimental results suggested that physical interaction was preferred in such matrix and nominate use of this new material to be used in the medical field as a result of dioxin illumination.